The Starting Point of the Performance, The Breaking Point of the Performance, The Percussion and Non-Percussion Point in Conducting - D. Raimova (Research Parks Publishing LLC, 2021)
This article provides information on the starting point of the conductor's technique, the breaking point, the percussion and non-percussion points. The student is instructed to start the performance in the conduction of the work - attention, auftakt, accuracy of the scheme, the need to pay attention to the conducting apparatus. It was noted that it is important to emphasize the artistic image of the work, as well as the importance of highlighting the points of impact and non-impact points through the conduction gestures of the means of artistic expression of the work. There are so many elements that it is important to put them into the final chord of the work, taking into account the fermats, pauses, and so on.